Whole-genome sequencing and comparative genomic analysis of Shewanella xiamenensis strains carrying blaOXA-48-like genes isolated from a water environment in Vietnam. (June 2020) - Nguyen, Nga Thi; Takemura, Taichiro; Pham, Anh Hong Quynh; Tran, Hien Thi; Vu, Kim Chi Thi; Tu, Nguyen Dong; Huong, Le Thanh; Cuong, Ngo Tuan; Kasuga, Ikuro; Hasebe, Futoshi; Suzuki, Masato
Abstract: Objectives: The aim of this study was to understand the natural bacterial hosts of antimicrobial resistance genes (ARGs) and their impact on the processes of evolution, spread and positive selection of acquired ARGs. Methods: Environmental carbapenem-resistant Gram-negative bacteria in Vietnam were screened for based on a One Health approach. Whole-genome sequencing (WGS) and comparative genomic analysis of the isolates were performed. WGS of three carbapenem-resistant Shewanella xiamenensis strains (SxND_W2_2018, SxND_W5_2018 and SxND_W9_2018) isolated from canals in Truc Ninh District and Nghia Hung District, Nam Dinh Province, Vietnam, in 2018 was performed using an Illumina MiniSeq system. ARGs in the draft genome sequences were detected using ResFinder, and comparison of genomic regions was performed using BLASTn and Easyfig. Results: The bla OXA-48 -like carbapenem-hydrolysing class D β-lactamase genes bla OXA-48, bla OXA-252 and bla OXA-547 were detected in chromosomal contigs of SxND_W2_2018, SxND_W5_2018 and SxND_W9_2018, respectively. Comparative analysis of the surrounding regions of the bla OXA-48 -like genes, including both 10 kb upstream and 10 kb downstream of the genes, showed that the genomic regions were highly conserved in all three isolates. Conclusion: This study analysed the draft genome sequences of carbapenem-resistant S. xiamenensis strains isolated from a water environment in Vietnam. All of the strains carried bla OXA-48 -like gene variants in their chromosomes. This information will contribute to highlight the evolution of bla OXA-48 family carbapenemase genes in nature and the importance of S. xiamenensis as a natural reservoir of important ARGs in the environment in Vietnam.